MATHEMATICAL MODELING OF TRANSITION HEAT AND HYDRAULIC PROCESSES IN THE WATER TUBE HEATING SYSTEM WITH RADIATOR THERMOSTATS (Academic journal Industrial Machine Building Civil Engineering, 2017)
The modern building normative base Ukraine provides installation radiator thermostaton heating devices water heating systems. In spite of the declared producers energy-efficienteffect in 10 – 20% of the annual cost of heat and comparatively not high cost, the energy savingmeasure is not widely spread in Ukraine. It is related to number of peculiarities of domestic ofsystems heating: use of hydraulic elevator thermal units, a small number of buildings equippedwith heat counters, the constant hydraulic regime of systems heating and district heating, etc.This work is devoted to investigation of thermal and hydraulic regimes of tube heating systemswith thermostatic controls.For the simulation transient thermal and hydraulic regimes of heating systems withradiator thermostats in this paper proposed of the mathematical model. Its peculiarity is acomprehensive consideration of various factors (both disturbing and regulating) on the thermaland hydraulic modes of work automated heating system. This mathematical model can be usedto create computer programs and perform a variety of researches in the field automatic controlthermal mode of premises. The research results can be applied to the design and optimizationof modern control systems tempering heat.Keywords: mathematical model, heating system, thermostatic valve.